Ready Wicaksono1*) dan Mispiyant PENGARUH KARAKTERISTIK PERSONAL DAN FAKTOR SITUASIONAL DALAM PENERIMAAN PERILAKU DISFUNGSIONAL TERHADAP KUALITAS AUDIT: 1)Program Studi Akuntansi, Sekolah Tinggi Ilmu Ekonomi Balikpapan 2) Program Studi Akuntansi, Sekolah Tinggi Ilmu Ekonomi Putra Bangsa *e-mail: ready@stiebalikpapan.ac.id - Ready Wicaksono1*) dan Mispiyanti 2) (GREENOMIKA, 2019)
This study aims to determine the effect of personal characteristics and situational factors in accepting dysfunctional behavior on audit quality. The population is all individuals who are public auditors in the Special Province of Yogyakarta and Central Java and the study sample is 300 respondents. The sampling technique uses the random sampling method. Data analysis used The Structural Equation Modeling (SEM) of the AMOS statistical software package in the model and hypothesis assessment. The results of this study prove that the locus of control has a positive effect and the desire to stop working has a positive effect on dysfunctional behavior, performance harms dysfunctional behavior. Leadership style negatively affects dysfunctional behavior. Locus of control has a positive effect on audit quality, the desire to stop working has no significant effect on audit quality, performance has a significant positive effect on audit quality, leadership style does not significantly influence audit quality and dysfunctional behavior has a significant negative effect on audit quality.